Glycemic and non-glycemic targets in younger and older North Indian subjects with type 2 diabetes in a Tertiary care hospital: A 10 year's retrospective data analysis. Issue 1 (January 2016) - Ahmad, Jamal; Zubair, Mohammad; Malik, Nelofar; D, Zephy; Raghav, Alok
Abstract: Background: Although optimizing glycemic and non-glycemic targets reduced micro- and macro-vascular complications in type 2 diabetes, multiple barriers hinder turning evidence into practice. Mounting evidence suggests that those with onset of disease in early or mid-adult life, compared with those with onset at an older age, may have a more severe disease course and worse glycemic control. Aims & objective: We tested the hypothesis that those diagnosed at younger age would have worse glycemic control, even after adjustment for duration of diabetes, higher BMI and other known risk factors for worse glycemic control. Materials & methods: A cross-sectional analysis of 560 type 2 diabetic subjects from North Indian populace in the year 1999–2012 who reported to endocrine clinic was performed. Sixty patients did not report in the successive year and final data analyses were done in 500 patients attending clinic regularly over a period of 10 years for evaluation of glycemic and non-glycemic targets. They were followed up at 3 monthly intervals with all patients undergoing anthropometric measurement (BMI (weight in kg/height in m 2 ), diet and lifestyle advice by a diabetic educator and consultation by endocrinologist. Fasting and postprandial plasma glucose, A1c (3 monthly), besides evaluation of SMBG that was performed in 50% of these patients regularly. Fasting lipids, S. creatinine and microalbuminuria were assessed annually and blood pressure recoding was done at each visit. The treatment was modified as per the investigation reports. We classified age at diabetes diagnosis as younger (<60 years) vs older (≥60 years). The primary outcome of interest was HbA1c ≥9%. Secondary outcomes were HbA1c ≥8% to <9% and HbA1c ≥7% to <8%. Results: After adjustment for sex, duration of diabetes, hyperglycemic medications, BMI, co-morbid conditions, age <60 years at diagnosis remains significantly associated with greater odds of HbA1c ≥9% [OR 0.95(0.84–1.07)], HbA1c ≥8% to <9% [OR 1.04(0.93–1.15)] and HbA1c ≥7% to <8% [OR 1.05(0.85–1.17)] for female sex. Seventy two (72.7%) of patients <60 years achieved BP <140/90 mmHg ( p < 0.001) as compared to 62.3% of patients ≥60 years who achieved BP <150/90 mmHg ( p < 0.001) and LDL-cholesterol <100 mg/dl in 33.7% patients and 39.1% respectively ( p < 0.002). Conclusion: Younger age (<60 years) at type 2 diabetes diagnosis is significantly associated with worse subsequent glycemic control and lipid control, as younger patients at diagnosis have fewer competing co-morbidities and complications. As patient-centeredness is a priority in type 2 diabetes care, safe, aggressive and individualized treatment could benefit this higher-risk group.